Effects of soil management strategies based on different principles on soil microbial communities and the outcomes for plant health - Xing Zhou; Qian Zhang; Yuanyuan Yan; Jisong Qu; Jun Zhou; Jun Zhao; Jinbo Zhang; Zucong Cai; Chuanchao Dai; Xinqi Huang (Biological Control)
Various soil management strategies based on chemical, physical, and biological principles are used to manipulate soil microbial communities to improve plant health. However, how the microbial communities that are altered by these strategies respond to pathogen invasion and contribute to plant health remains poorly understood. Here, we investigated the effects of representative chemical, physical, and biological strategies, namely, chemical fumigation (CF), heat disinfestation (HE), and reductive soil disinfestation (RSD), on soil microbial communities, pathogen invasion, and plant performance. Our results revealed a strong relationship between variations in soil microbial communities and their impact on pathogen inhibition and plant health under the different strategies. Physicochemical management effectively decreased the density of Fusarium oxysporum, thereby suppressing the outbreak of Fusarium wilt. However, these strategies also decreased fungal density, bacterial diversity, network complexity, and core microbiome stability, resulting in diminished pathogen resistance and the recurrence of plant disease upon pathogen reinoculation. In contrast, biological management was the most effective strategy for the suppression of pathogen invasion and the improvement of plant health. Biological management optimized the bacterial and core microbiomes, leading to increased bacterial diversity and stimulated the growth of potential disease-suppressive agents, which contributed to resistance to F. oxysporum invasion and consistently prompted plant health. Taken together, our results reveal that physicochemical (CF and HE) and biological strategies (RSD) contribute to plant health via different mechanisms. In addition, this study provides empirical evidence for the significant impact of biological management on the manipulation of the core microbiome and its critical role in plant health.